Gender and migration: Employment of rural migrants in South China's factories. Issue 3 (2nd July 2016) - Guo, Chunlan; Shen, Jianfa
Abstract : Drawing on rural migrants' experiences and narratives collected through in-depth fieldwork in the Pearl River Delta in 2008–2009, we discovered that rural women are more successful than men in securing factory employment. We looked at the ways in which the employment of rural migrants in South China's factories was an outcome of the interweaving of gender, migrant status, the segmented labor market, and the hukou (household registration) system. The factories have tended to recruit women as it is believed that femininity can contribute to increasing production efficiency, creating a "safe" space for production and minimizing labor costs. At the same time, masculinity is associated with "carelessness, " "laziness, " "naughtiness, " "conflict, " "violence, " and "trouble-makers." In addition, the identity of "migrant" has helped women break free from the traditional gender regime and strengthen their labor market participation.